2004
DOI: 10.1037/0894-4105.18.4.756
|View full text |Cite
|
Sign up to set email alerts
|

Puzzling Thoughts for H. M.: Can New Semantic Information Be Anchored to Old Semantic Memories?

Abstract: Researchers currently debate whether new semantic knowledge can be learned and retrieved despite extensive damage to medial temporal lobe (MTL) structures. The authors explored whether H.M., a patient with amnesia, could acquire new semantic information in the context of his lifelong hobby of solving crossword puzzles. First, H.M. was tested on a series of word-skills tests believed important in solving crosswords. He also completed 3 new crosswords: 1 puzzle testing pre-1953 knowledge, another testing post-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
37
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 81 publications
(190 reference statements)
8
37
0
Order By: Relevance
“…To this extent, H.M. solves crossword puzzles competently and demonstrates the necessary word-retrieval skills. This result is consistent with a previous study in which H.M. performed between one and two standard deviations of the means of healthy volunteers on various measures of cognitive function believed to underlie skill in solving crossword puzzles (Skotko et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To this extent, H.M. solves crossword puzzles competently and demonstrates the necessary word-retrieval skills. This result is consistent with a previous study in which H.M. performed between one and two standard deviations of the means of healthy volunteers on various measures of cognitive function believed to underlie skill in solving crossword puzzles (Skotko et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…Skotko et al (2004) observed that in a laboratory setting, H.M. typically solved his crossword puzzles in a linear fashion: He began with 1 Across, completed the Across clues, and then completed the Down clues. He did not benefit from the crisscrossing nature of the puzzles while completing the Across clues.…”
Section: Resultsmentioning
confidence: 99%
“…The cause of the amnesia was surgical resection of medial temporal lobe structures to control otherwise uncontrollable epileptic seizures. Among the numerous published studies of the effects of the procedure on H.M.'s cognitive abilities, one by Skotko et al (2004) was prompted by the fact that H. M., then a man in his early 70s, had made a hobby of crossword puzzles over his entire adult life. He regularly solved them before and after his surgery.…”
Section: Some Theoretical Questions and Conjecturesmentioning
confidence: 99%
“…H.M. could not associate the correct definitions to the words despite hundreds of trials of training (Gabrieli et al, 1988). Since that time, a number of studies have reported some learning of semantic information in amnesic patients, although learning is impaired compared with that exhibited by control subjects (Tulving et al, 1991;Hamann and Squire, 1995;Kitchner et al, 1998;Verfaellie et al, 2000;Westmacott and Moscovitch, 2001;Bayley and Squire, 2002;Corkin, 2002;Schmolck et al, 2002;Skotko et al, 2004). It may not be surprising that the capacity for new semantic learning is constrained and impoverished relative to healthy controls, likely because having access to hippocampal-based representations aid in acquisition and expression of new semantic learning in general (Tulving et al, 1991).…”
Section: Human Evidencementioning
confidence: 99%